USING ROSETTA STONE AS LEARNING MEDIA TO INCREASE SPEAKING SKILL FOR JUNIOR HIGH SCHOOL STUDENTS - Peby Yurdean; An Fauzia Rozani Syafei (Journal of English Language Teaching, 2016)
English teaching is increasingly growing as time advances. Using new technologies are already widely used in teaching, but there are still some obstacles often encountered. Using the same method or media in learning English is still used by teachers because of the limited knowledge of other methods or media. This makes learning look stiff and unattractive, students became bored in the learning process, especially in the teaching of speaking. To resolve this issue, teachers need to require alternative solutions to overcome those difficulties. One of them is uses technology-based teaching that called CAI. This paper describes about the use of Rosetta Stone, one tool of CAI. Rosetta Stone is an interactive software for teaching foreign languages to beginners. This software can be used as a medium by teachers in teaching English to Junior High School students in enhancing the ability of Speaking. This program does not use the idea or concept to use a translation to remember a new language. Instead itcombine words, sounds and images from real life to provide information about the new language without translation.